2014
DOI: 10.1161/circresaha.114.302734
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Contagion Induced by Parkin Deficiency in Drosophila Hearts and Its Containment by Suppressing Mitofusin

Abstract: Rationale Dysfunctional Parkin-mediated mitophagic culling of senescent or damaged mitochondria is a major pathological process underlying Parkinson disease and a potential genetic mechanism of cardiomyopathy. Despite epidemiological associations between Parkinson disease and heart failure, the role of Parkin and mitophagic quality control in maintaining normal cardiac homeostasis is poorly understood. Objective We used germline mutants and cardiac-specific RNA interference to interrogate Parkin regulation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
116
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(124 citation statements)
references
References 37 publications
7
116
1
Order By: Relevance
“…Interestingly, downregulation of Beclin1 did not affect GD-induced increases in mitochondrial foreshortening (Online Figure VC) but significantly increased GD-induced cell death (Online Figure VD). Thus, although evidence suggests that unopposed fusion of mitochondria alone can induce cell death, 27 suppression of autophagy alone may also induce cardiomyocyte death even when mitochondrial foreshortening is not affected.…”
Section: Prolonged Treatment With Mdivi-1 Mimics the Effect Of Drp1 Dmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, downregulation of Beclin1 did not affect GD-induced increases in mitochondrial foreshortening (Online Figure VC) but significantly increased GD-induced cell death (Online Figure VD). Thus, although evidence suggests that unopposed fusion of mitochondria alone can induce cell death, 27 suppression of autophagy alone may also induce cardiomyocyte death even when mitochondrial foreshortening is not affected.…”
Section: Prolonged Treatment With Mdivi-1 Mimics the Effect Of Drp1 Dmentioning
confidence: 99%
“…Furthermore, 1-time treatment with mdivi-1 reduced I/R injury even in Drp1-hetCKO mice, suggesting that mdivi-1 most likely has a Drp1-independent antiapoptotic function. Along this same line, mdivi-1 affects other molecules besides Drp1, including delayed rectifier K + channels, 27 raising the issue of specificity of the chemical inhibitor. Fourth, mitochondrial localization of Drp1 is positively regulated by protein kinase A, 30 calcineurin, 30 PUMA, 31 Bax/Bak, 32 ceramide, 33 and O-linked-ÎČ-N-acetylglucosamine modification, 34 and is negatively regulated by miR-499 35 and Pim1.…”
Section: Ikeda Et Al Drp1 Mediates Autophagy 277mentioning
confidence: 99%
“…The mitochondrial network is under constant remodeling by fusion and fission. Mitochondrial fission, budding off parts of the mitochondrial network, is essential for the identification of dysfunctional and senescent parts of the mitochondrial network and their removal by autophagy [46,73]. In addition, mitochondrial fusion is required for mitochondrial maintenance; it is not only essential for cardiomyocyte differentiation [74], but also for the healthy function of an adult heart [4,75].…”
Section: Maintenance Of Heart Mitochondrial Homeostasismentioning
confidence: 99%
“…Over-expression of Cu/ZnSOD in the muscle and other tissues (twist-GAL4 driver) was reported to rescue the life-span shortening effect of a mutation in the parkin gene (Saini et al 2010), and over-expression of MnSOD was reported to reduce the developmental defects caused by a PINK1 gene mutation (Koh et al 2012). Over-expression of either Cu/ZnSOD or MnSOD was found to reduce the toxic effects of poly-Q-containing proteins in the Drosophila heart (Melkani et al 2013), and to reduce the toxic effects of disrupted mitochondrial fusion in the heart (Dorn et al 2011;Bhandari et al 2014). Over-expression of MnSOD increased survival of flies expressing the mutant protein associated with human spinal cerebellar ataxia type 12 (Wang et al 2011).…”
Section: Sod As Modifier Of Aging Phenotypesmentioning
confidence: 99%